Genetic reanalysis of patients with a difference of sex development carrying the NR5A1/SF-1 variant p.Gly146Ala has discovered other likely disease-causing variations - Martinez de Lapiscina, Idoia; Kouri, Chrysanthi; Aurrekoetxea, Josu; Sanchez, Mirian; Naamneh Elzenaty, Rawda; Sauter, Kay-Sara; Camats, Núria; Grau, Gema; Rica, Itxaso; Rodriguez, Amaia; Vela, Amaia; Cortazar, Alicia; et al. (PloS one, 2023)
NR5A1/ SF-1 (Steroidogenic factor-1) variants may cause mild to severe differences of sex development (DSD) or may be found in healthy carriers. The NR5A1 /SF-1 c.437G>C/p.Gly146Ala variant is common in individuals with a DSD and has been suggested to act as a susceptibility factor for adrenal disease or cryptorchidism. Since the allele frequency is high in the general population, and the functional testing of the p.Gly146Ala variant revealed inconclusive results, the disease-causing effect of this variant has been questioned. However, a role as a disease modifier is still possible given that oligogenic inheritance has been described in patients with NR5A1 /SF-1 variants. Therefore, we performed next generation sequencing (NGS) in 13 DSD individuals harboring the NR5A1 /SF-1 p.Gly146Ala variant to search for other DSD-causing variants and clarify the function of this variant for the phenotype of the carriers. Panel and whole-exome sequencing was performed, and data were analyzed with a filtering algorithm for detecting variants in NR5A1 - and DSD-related genes. The phenotype of the studied individuals ranged from scrotal hypospadias and ambiguous genitalia in 46,XY DSD to opposite sex in both 46,XY and 46,XX. In nine subjects we identified either a clearly pathogenic DSD gene variant (e.g. in AR ) or one to four potentially deleterious variants that likely explain the observed phenotype alone (e.g. in FGFR3 , CHD7 ). Our study shows that most individuals carrying the NR5A1 /SF-1 p.Gly146Ala variant, harbor at least one other deleterious gene variant which can explain the DSD phenotype. This finding confirms that the NR5A1/ SF-1 p.Gly146Ala variant may not contribute to the pathogenesis of DSD and qualifies as a benign polymorphism. Thus, individuals, in whom the NR5A1 /SF-1 p.Gly146Ala gene variant has been identified as the underlying genetic cause for their DSD in the past, should be re-evaluated with a NGS method to reveal the real genetic diagnosis.